Calcium Carbonate Precipitation for CO2 Storage and Utilization: A Review of the Carbonate Crystallization and Polymorphism - Chang, Ribooga; Kim, Semin; Lee, Seungin; Choi, Soyoung; Kim, Minhee; Park, Youngjune (Frontiers in Energy Research, 2017)
The transformation of CO2 into a precipitated mineral carbonate through an ex situ mineral carbonation route is considered a promising option for CO2 capture and storage (CCS) since (i) the captured CO2 can be stored permanently, and (ii) industrial wastes (i.e. coal fly ash, steel and stainless-steel slags, and cement and lime kiln dusts) can be recycled and converted into value-added carbonate materials by controlling polymorphs and properties of the mineral carbonates. The final products produced by the ex situ mineral carbonation route can be divided into two categories − low-end high-volume and high-end low-volume mineral carbonates− in terms of their market needs as well as their properties (i.e. purity). Therefore, it is expected that this can partially offset the total cost of the CCS processes. Polymorphs and physicochemical properties of CaCO3 strongly rely on the synthesis variables such as temperature, pH of the solution, reaction time, ion concentration and ratio, stirring, and the concentration of additives. Various efforts to control and fabricate polymorphs of CaCO3 have been made to date. In this review, we present a summary of current knowledge and recent investigations entailing mechanistic studies on the formation of the precipitated CaCO3 and the influences of the synthesis factors on the polymorphs.